Opioid substitution therapy is associated with increased detection of hepatitis C virus infection: A 15-year observational cohort study. (1st March 2015) - Larney, Sarah; Grebely, Jason; Falster, Michael; Swart, Alexander; Amin, Janaki; Degenhardt, Louisa; Burns, Lucinda; Vajdic, Claire M.
Highlights: Strategies are needed to increase detection of hepatitis C virus (HCV). We examined incident HCV notification in and out of opioid substitution therapy (OST). Incident HCV notification rates increased during OST. HCV screening in OST increases detection of HCV in people who inject drugs. Abstract: Background: Strategies are needed to enhance screening of hepatitis C virus (HCV) infection among people who inject drugs to improve engagement in HCV treatment, and stem the growing burden of HCV-related morbidity and mortality. Methods: We linked routinely collected data on enrolment in opioid substitution therapy (OST) and HCV notifications. We calculated rates of incident HCV notifications, and compared rates in and out of OST. Results: Following adjustment for sex, age and calendar period, rates of incident HCV notification were significantly higher during periods of OST, compared to periods out of OST (adjusted incident rate ratio: 1.91; 95% confidence interval: 1.86, 1.97). This effect was seen across multiple treatment periods. Conclusions: HCV screening in OST settings increases detection of HCV infection among people who inject drugs.